UTILIZATION OF HYACINTH BIOGAS (EICHORNIA CROSSIPES) AND GOAT DUNG (FAECES) AS ALTERNATIVE ENERGY SOURCES - Surachman, Surachman; Irawan, Hari; Ryan, Ryan (Nindikayla Institute, 2024)
Research has been conducted on using hyacinth biogas (Eichornia crossipes) and goat dung (faeces) as alternative energy sources. This research aims to design reactors, measure temperature, measure pH, conduct flame tests. This study shows that the temperature, pH, and composition of material comparison greatly influence the formation of biogas. The ratio of hyacinth mass and water used is 1.1, 1:2, and 1:3 with each ratio given goat dung as much as 400 grams. All treatments produce a gas that can ignite. Heat produced is between 12.75 calories to 16.6 calories.